PASTORAL VISION ON EDUCATION: Foresight of an Educationist, Kuriakose Elias Chavara - Punneliparambil, Sunny (Journal of Dharma, 2006)
Man shares in the light of God’s mind. He is justified in considering himself as an intellectual being who is superior to the material world around him, as he always searches for fundamental truths. He realizes his true and full human potential, by cultivating the gifts and values of his nature, and thus acquiring a high degree of culture. In the life of man culture and nature are closely interrelated. He has co-responsibility with his fellow human beings and the society at large. This co-responsibility is evolved through certain basic human values. This value system is evolved in the society as well as in the human being through the processes of education. Education should act as a powerful agent of liberation of the individual as well as the society. It must liberate the creative potentialities of human consciousness. Through educational processes we should aim the integral wellbeing of the humankind, by contributing to the development of true human culture.